2019
DOI: 10.1016/j.gde.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of eukaryotic transcription factors

Abstract: Transcription factors (TFs) have a central role in genome regulation directing gene transcription through binding specific DNA sequences. Eukaryotic genomes encode a large diversity of TF classes, each defined by unique DNA-interaction domains. Recent advances in genome sequencing and phylogenetic placement of diverse eukaryotic and archaeal species are redefining the evolutionary history of eukaryotic TFs. The emerging view from a comparative genomics perspective is that the Last Eukaryotic Common Ancestor (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 55 publications
(71 reference statements)
0
40
0
Order By: Relevance
“…This contribution rate was significantly reduced in other tissues and isoforms with high expression abundance in different tissues were altered, further demonstrating that AS was involved in the regulation of gene expression of TSGs. In addition, earlier work has shown that TFs were vital in gene regulatory networks [26,39]. Transcriptome analysis was used here to define key TFs in porcine TSGs regulation, including TCF7L1 and THRB.…”
Section: Discussionmentioning
confidence: 99%
“…This contribution rate was significantly reduced in other tissues and isoforms with high expression abundance in different tissues were altered, further demonstrating that AS was involved in the regulation of gene expression of TSGs. In addition, earlier work has shown that TFs were vital in gene regulatory networks [26,39]. Transcriptome analysis was used here to define key TFs in porcine TSGs regulation, including TCF7L1 and THRB.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge points to the fact that, across the tree of life, prior to and during major radiations of new species, there comes a commensurate increase in the number of regulatory genes. Comparative genomic analyses suggest that at the time of eurkaryogenesis, or the origin of the last eukaryotic ancestor (LECA), a significant increase in novel TF classes occurred [69]. Eukaryogenesis is one of the major transitions of life on Earth, with an explosion of diversity owing to the endosymbiotic synthesis of an energy producing α-proteobacteria mitochondrion-progenitor within an archaeon [70].…”
Section: Regulatory Changes Drive Evolutionmentioning
confidence: 99%
“…DBDs are responsible for TF DNA binding specificity and affinity. At the sequence level, DBD are quite conserved across Streptophytes and most of the observed genetic diversity is explained by gene duplication events where a similar DBD is conserved (Catarino et al, 2016;de Mendoza & Sebé-Pedrós, 2019). Studies of several TFs demonstrated that the DNA binding specificity is…”
Section: How Do Transcription Factors Evolve?mentioning
confidence: 99%